Fecal microbiome and hippocampal volume in children - Aaros, Julia (My University, 2025)
The gastrointestinal (GI) microbiome is not stable immediately after birth. Early GI microbiome composition is influenced by multiple factors, such as early antibiotic use and birthing method. Similarly, the hippocampal volume continues to grow rapidly during the first three years of life. Numerous studies have suggested a correlation between brain development and the GI microbiome. The purpose of this research was to determine whether there is a significant correlation between the fecal microbiome and hippocampal volume. Specifically, the associations between intestinal microbiome alpha and beta diversity and hippocampal volumes were investigated. Data for this cross-sectional study was collected from the FinnBrain Birth Cohort study. The participants included families from the city of Turku, nearby municipality of Turku and Åland. The sample included 82 children who delivered a fecal sample at the age of 2,5 months. MRI scans were conducted at 5 years of age. No statistically significant linear correlation was between alpha diversity and left hippocampal volume (p = 0.711) or right hippocampal volume (p = 0.2617). Similarly, there was no significant correlation between beta diversity and left hippocampal volume (F. Model = 0.737, Pr (> F) = 0.76) or between beta diversity and right hippocampal volume (F. Model = 1. 2205, Pr (> F) = 26). The results differed from previous studies. While prior research has demonstrated associations between alpha diversity and brain development as well as beta diversity and brain, these relationships have not been clearly established at this specific age point. Future studies are needed to achieve better understanding of correlations between brain and GI microbiome.
Keywords: alpha diversity, beta diversity, hippocampus, GI microbiome